Diagnóstico integral al área de mantenimiento de una empresa del sector servicios en aire acondicionado del Valle de Aburrá (2012)
The integral maintenance management is based on actively interacting, searching for the best results in all the processes that are related directly, as well as indirectly with the maintenance area of the company -- This project aims to apply an audit methodology maintenance management to the AC services company, with the purpose of obtaining a diagnosis of the company’s maintenance area -- By focusing on finding and enhancing the most susceptible topics in need of improvement, the company will be able to position itself as a leader in the regional market